2021
DOI: 10.1177/17479541211017276
|View full text |Cite
|
Sign up to set email alerts
|

Post-match video-based feedback: A longitudinal work-based coach development program stimulating changes in coaches’ knowledge and understanding

Abstract: The literature regarding formal coach education and development highlights issues of transference of usable knowledge to the real-world context. This study sought to engage coaches from a Spanish football academy in a longitudinal work-based coach development program (CDP) focused on the delivery of post-match feedback. The CDP was delivered over a 23-month period through collaboration between a sport pedagogue researcher-practitioner, the Academy Management Team, and an experienced research team. The study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Taken together, it remains not only necessary to record the pedagogical behaviors of coaches, but to also reflect upon the appropriateness of such behaviors for developing desired outcomes. Particularly as it is well-demonstrated that some coaches have limited awareness of how they behave in various ways, with athletes' ratings correlating more strongly with observed behaviors than the coaches' own self-ratings (e.g., Harvey et al, 2013 ; Partington and Cushion, 2013 ; Raya-Castellano et al, 2021 ). Low self-awareness among coaches is well-evidenced, coaches are unaware of their moment-to-moment behavior (De Marco et al, 1996 ).…”
Section: Systematic Observation and Sport Coachingmentioning
confidence: 99%
See 4 more Smart Citations
“…Taken together, it remains not only necessary to record the pedagogical behaviors of coaches, but to also reflect upon the appropriateness of such behaviors for developing desired outcomes. Particularly as it is well-demonstrated that some coaches have limited awareness of how they behave in various ways, with athletes' ratings correlating more strongly with observed behaviors than the coaches' own self-ratings (e.g., Harvey et al, 2013 ; Partington and Cushion, 2013 ; Raya-Castellano et al, 2021 ). Low self-awareness among coaches is well-evidenced, coaches are unaware of their moment-to-moment behavior (De Marco et al, 1996 ).…”
Section: Systematic Observation and Sport Coachingmentioning
confidence: 99%
“…This issue is not unique to coaching but has been found in other educational domains (i.e., Hook and Rosenshine, 1979 ), as well as physical activity settings (i.e., McKenzie, 2016 ). Any advances in coach education and development would likely be fruitless if coaches lack basic levels of self-awareness, particularly in practice environments driven by a strong sub-culture (Cushion et al, 2012b ; Partington et al, 2015 ; Raya-Castellano et al, 2021 ).…”
Section: Systematic Observation and Sport Coachingmentioning
confidence: 99%
See 3 more Smart Citations